COMBINED IN SITU X-RAY DIFFRACTION AND RAMAN SPECTROSCOPY ON MAJORITIC GARNET INCLUSIONS IN DIAMONDS - Kunz M.; Gillet P.; Fiquet G.; Sautter V.; Graafsma H.; Conrad P.; Harris J. (My University, 2002)
Mineral inclusions in Sao Luiz diamonds have been characterized using angle dispersive X-ray diffraction and Raman spectroscopy. We identified two different garnet phases coexisting with an omphacitic pyroxene. They represent disintegration products of a former homogeneous majorite-rich garnet phase. The two garnets have significantly different cell parameters but are tightly intergrown with their unit cells parallel to each other. The garnets are oriented relative to the diamond host with [100]garnet parallel to [110]diamond. Combining the measured cell parameters of the garnet inclusions with chemical analyses of similar inclusions from the same source allows the extraction of a residual pressure between 1 and 3 GPa, depending on the exact chemical composition assumed. Depth-resolved Raman spectra at the diamond-garnet interface indicate a residual pressure of about 1 GPa. Such a low residual pressure is unexpected at first glance for a garnet assemblage from the transition zone. The inclusion pressure is lowered due to pyroxene crystals, which surround the garnet inclusions and act as cushions reducing the residual inclusion pressure.
Keywords: DIAMOND INCLUSIONS; MAJORITE; OMPHACITE; TRANSITION ZONE